Pengaruh Komite Audit, Good Corporate Governance dan Whistleblowing System terhadap Fraud Bank Umum Syariah di Indonesia Periode 2016-2019 - Maisaroh, Phuji; Nurhidayati, Maulida (UIN Kiai Ageng Muhammad Besari Ponorogo, 2021)
Fraud relates to fraudulent acts committed deliberately through bank facilities and resulting in losses. Although the role of the audit committee has been established, Good Corporate Governance has generally been well implemented, and has carried out a fairly good internal control function through the Whistleblowing System, the fulfillment of these components has not significantly been able to overcome fraud. Such an interesting condition to be related to the theory of Rezaae and Ajeng Wind. This study is intended to examine the effect of the audit committee, Good Corporate Governance, and the Whistleblowing System on fraud either partially or simultaneously. Sharia Commercial Banks for the period 2016-2019 in Indonesia were selected as the population using saturated sampling techniques, there are 14 Islamic Commercial Banks with 56 units of analysis used in this study. Ordinal logistic regression model was chosen as an analysis technique with SPSS 21 software as an analysis tool. The results of this study indicate that the variable composition of the independent audit committee, tenure of the audit committee and good corporate governance has a significant negative relationship to fraud. Meanwhile, the audit committee meeting variables and the Whistleblowing System have a negative and insignificant effect on fraud. The independent variable composition of the audit committee, audit committee meetings, tenure of the audit committee, Good Corporate Governance, and the Whistleblowing System is able to explain the variation of fraud by 29% while the remaining 71% is explained by other variables outside the research model. The low level of influence may be due to the inadequate follow-up of the audit committee meetings and the lack of independence of the internal auditors in managing fraud reports. So that Sharia Commercial Banks must optimize the function of the anti-fraud division and present the division in holding meetings, as well as increase the independence of the internal auditors in managing reports of suspected fraud that are submitted through the Whistleblowing System.Fraud berkaitan dengan tindakan kecurangan yang dilakukan secara sengaja melalui sarana bank dan mengakibatkan kerugian. Meskipun peranan komite audit telah terbentuk, Good Corporate Governance secara umum telah diterapkan dengan baik, serta menjalankan fungsi pengendalian internal melalui Whistleblowing System yang cukup baik, namun pemenuhan komponen-komponen tersebut tidak secara signifikan mampu mengatasi fraud. Kondisi yang demikian menarik untuk dihubungkan dengan teori Rezaae dan Ajeng Wind. Penelitian ini dimaksudkan untuk menguji pengaruh komite audit, Good Corporate Governance, dan Whistleblowing System terhadap fraud baik secara parsial maupun simultan. Bank Umum Syariah di Indonesia periode 2016-2019 dipilih sebagai populasi dengan menggunakan teknik sampling jenuh, ada 14 Bank Umum Syariah dengan 56 unit analisis yang digunakan dalam penelitian ini. Model regresi logistik ordinal dipilih sebagai teknik analisis dengan software SPSS 21 sebagai alat bantu analisis. Hasil penelitian ini menunjukkan variabel komposisi komite audit independen, masa tugas komite audit dan Good Corporate Governance memiliki hubungan yang negatif signifikan terhadap fraud. Sedangkan variabel rapat komite audit dan Whistleblowing System berpengaruh negatif tidak signifikan terhadap fraud. Variabel independen komposisi komite audit, rapat komite audit, masa tugas komite audit, Good Corporate Governance, dan Whistleblowing System mampu menjelaskan variasi fraud sebesar 29% sedangkan 71% sisanya dijelaskan oleh variabel lain diluar model penelitian. Rendahnya pengaruh yang diberikan tersebut kemungkinan disebabkan oleh kurang optimalnya tindak lanjut dari rapat komite audit yang diselenggarakan serta kurangnya independensi auditor internal dalam mengelola laporan fraud. Sehingga Bank Umum Syariah harus mengoptimalkan fungsi divisi anti fraud dan menghadirkan divisi tersebut dalam penyelenggaraan rapat, serta meningkatkan independensi auditor internal dalam mengelola laporan dugaan fraud yang masuk melalui Whistleblowing System.